Breeding Soundness Evaluation of the Bull - Páez-Barón, Edwin Manuel; Corredor-Camargo, Emma Sofía (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The breeding soundness evaluation of the bull is a simple, practical and inexpensive test that allows the identification of subfertile and infertile animals that may affect the success of a breeding program. It should be performed periodically, but its use in our country is uncommon. This assessment involves three basic steps: physical examination (general shape, internal and external sex organs), evaluation of the libido, and the collection and evaluation of semen. A review of issues that includes reproductive bull evaluation in order to determine the reproductive fitness of males intended for that purpose is presented here.